Políticas territoriais em tempos de múltiplas crises: Desafios e perspectivas para o Brasil na década de 2020 - Aristides Monteiro Neto; Luciléia Aparecida Colombo; Jo\~ao Mendes da Rocha Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Global turmoils of diverse nature - economic, political, pandemics, and environmental - have become frequent and cumulative in the environment of contemporary government policies since the mid-2000s. In Brazil, economic recession, crisis of political representation, reforms, misadjustments and disassembly of policies have been a constant since 2015 affecting policies concerned to territorial dimension (regional, urban and rural). In this article, we discuss the implications of multiple crises on official Brazilian regional policy (Política Nacional de Desenvolvimento Regional - PNDR). We point out, on the one hand, the need to renew its objectives by incorporating an environmentally sustainable structural change agenda by simultaneous attention to two issues seen as essential: i) climate change and energy transition; and ii) increasing regional systemic productivity by making efforts in innovative capacity. On the other hand, internal problems on governance and policy management - low level of federative coordination, fragile legitimacy, among others - need to be addressed to ensure the effectiveness of government actions designed to promote growth without inequalities.
Keywords: O20; R58; 330; territorial policies; structural change; regional development